2021
DOI: 10.31083/j.rcm2203080
|View full text |Cite
|
Sign up to set email alerts
|

Current management and prognosis of patients with recurrent myocardial infarction

Abstract: Recurrent myocardial infarction (re-MI) is a common event following acute coronary syndrome (ACS), especially during the first year. According to epidemiological studies, patients who experience re-MI are at higher risk of all-cause cardiovascular events and mortality. The cornerstones of re-MI prevention include complete functional coronary revascularization, effective dual antiplatelet therapy and secondary prevention strategies. Notwithstanding this, some controversy still exists on the definition and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
0
4
0
1
Order By: Relevance
“…The present study provides unique contemporary data on clinical characteristics, healthcare resource utilization, and treatment patterns of patients at their first MI or with multiple MIs managed by cardiologists in routine clinical practice. Although several studies have evaluated the impact of re-MI on outcomes [ 1 9 ], this is the first study, to the best of our knowledge, that has demonstrated the incremental association between clinical risk and the increase in the number of re-MI events. Patients with multiple MIs were older and presented more comorbidities, more frequently underwent invasive testing within the previous 12 months from enrolment such as coronary angiography, and were more aggressively treated with pharmacological therapies compared to patients at their first MI event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study provides unique contemporary data on clinical characteristics, healthcare resource utilization, and treatment patterns of patients at their first MI or with multiple MIs managed by cardiologists in routine clinical practice. Although several studies have evaluated the impact of re-MI on outcomes [ 1 9 ], this is the first study, to the best of our knowledge, that has demonstrated the incremental association between clinical risk and the increase in the number of re-MI events. Patients with multiple MIs were older and presented more comorbidities, more frequently underwent invasive testing within the previous 12 months from enrolment such as coronary angiography, and were more aggressively treated with pharmacological therapies compared to patients at their first MI event.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of re-MI may be dramatic in patients surviving after a first coronary event [ 14 19 ]. Compared to patients without re-MI, those who suffer re-MI showed significantly higher rates of mortality at short- and long-term follow-up [ 1 9 , 14 19 ]. A recent paper, analyzing a prospective cohort of 3387 patients, showed that re-MI was associated with 25-fold higher risk of death at 1 year compared to patients with a single acute coronary event [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Такой вывод делается в ряде обзорных статей недавнего времени. Как отмечают De Luca L, et al [18], в настоящее время данных доказательной медицины недостаточно, чтобы определить специфику лечения повторного ИМ, как в острой фазе, так и в отдаленном периоде.…”
Section: кардиоваскулярная терапия и профилактика 2024;23unclassified
“…Patients with ACS recurrence within 1–2 years after the index event constitute 10–20% of patients admitted for ACS and have an extremely higher short- and medium-term risk of CV events and mortality than patients with no history of ACS events. 91 In the EYESHOT POST-MI study which included ∼1600 patients with myocardial infarction in 165 Italian cardiology centres, 13% had a history of 2 and 5% more than three infarct events. The latter had more risk factors and were older than patients at their first ACS event.…”
Section: Extreme Risk and Elderly Patientsmentioning
confidence: 99%